Electrophoretically induced aqueous flow through single-wall carbon nanotube membranes - Wu, Ji (2012)
Electrophoresis, the motion of charged species through liquids and pores under an external electric field, has been principle source of chemical pumping for numerous micro- and nano-fluidic devices platforms. Recent studies of ion current through single or few carbon nanotube channels range from near bulk mobility to 2-7 orders of magnitude of enhancement but cannot directly measure ion flux. Membranes, with large number of nanotube pores, allow independent confirmation of ion current and flux. Here we report that the aqueous electrophoretic mobility of ions within the graphitic cores of carbon nanotube membranes, with a uniform pore size of 0.9 ± 0.2 nm, is enhanced ∼3 times that of bulk mobilities. The induced electroosmotic velocities are 4 orders of magnitude faster than those measured in conventional porous materials. We also show that a nanotube membrane can function as a rectifying diode due to ionic steric effects within tightly controlled nanotube diameter.